2014
DOI: 10.1093/infdis/jiu574
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence due to Relapse or Reinfection WithMycobacterium tuberculosis: A Whole-Genome Sequencing Approach in a Large, Population-Based Cohort With a High HIV Infection Prevalence and Active Follow-up

Abstract: Background. Recurrent tuberculosis is a major health burden and may be due to relapse with the original strain or reinfection with a new strain.Methods. In a population-based study in northern Malawi, patients with tuberculosis diagnosed from 1996 to 2010 were actively followed after the end of treatment. Whole-genome sequencing with approximately 100-fold coverage was performed on all available cultures. Results of IS6110 restriction fragment-length polymorphism analyses were available for cultures performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
161
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(179 citation statements)
references
References 32 publications
11
161
1
1
Order By: Relevance
“…This could have biased the estimation of the effect of several demographic and clinical factors towards the null; it might also have resulted in an overestimation of relapse risk associated with HIV coinfection. Given that relapse is more likely to occur soon after treatment completion,36 we performed a sensitivity analysis examining outcomes at 12 months post-treatment completion with no substantive change in results. Last, we analysed the per-protocol analysis sets from RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…This could have biased the estimation of the effect of several demographic and clinical factors towards the null; it might also have resulted in an overestimation of relapse risk associated with HIV coinfection. Given that relapse is more likely to occur soon after treatment completion,36 we performed a sensitivity analysis examining outcomes at 12 months post-treatment completion with no substantive change in results. Last, we analysed the per-protocol analysis sets from RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies suggest that individuals with TB-cured history are susceptible to recurrent TB [1924]. This observation implies that TB-cured persons may have underlining immune incompetence.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, no studies have been undertaken to investigate whether the population with previously tuberculosis-cured history (TB-cured) can develop reduced immune responses and immunity after PPV23 vaccination. This is not a trivial question, as multiple clinical or epidemiology studies have reported that TB-cured individuals have higher rates of re-infection TB or TB relapse in the absence or presence of HIV coinfection [1924]. In addition, it is rational to study anti-TB and anti-pneumococcal responses in the context of PPV23 vaccination, as clinical studies have reported high co-incident rates of pneumococcus pneumonia and Mycobacterium tuberculosis (Mtb) infection irrespective of HIV infection [2528].…”
Section: Introductionmentioning
confidence: 99%
“…If reactivation were simply the result of a secondary infection acquired by proximity with an infectious host, there was no reason to believe that persisters were anything more than dying M. tuberculosis , incapable of causing disease. However, population-based epidemiologic studies, combined with molecular strain typing methods, showed that disease relapse in countries with low burden was largely due to the same strain causing the initial episode of disease, suggestive of reactivation (1518), while relapse in high burden areas was associated with different strains, suggestive of re-infection (19, 20). Work by Vandiviere, comparing bacilli recovered from resected lesions of patients receiving chemotherapy that were either in communication with (open) or closed off (closed) from the airways, showed that bacteria recovered from closed lesions were uniformly drug susceptible, while those from open lesions were drug resistant despite similar levels of drug penetration (21).…”
Section: Modelsmentioning
confidence: 99%